Impact of oxidative stress on treatment outcomes in adult patients with sepsis: A prospective study. Issue 26 (26th June 2020) - Hsiao, Sheng-Yuan; Kung, Chia-Te; Su, Chih-Min; Lai, Yun-Ru; Huang, Chin-Cheng; Tsai, Nai-Wen; Wang, Hung-Chen; Cheng, Ben-Chung; Su, Yu-Jih; Lin, Wei-Che; Chiang, Yi-Fang; Lu, Cheng-Hsien
Abstract: Purpose: Oxidative stress has been shown to reflect on the development of sepsis and disease severity. In the present study, we evaluated the effects of increased levels of oxidative stress and decreased antioxidant coactivity in patients with sepsis, and the importance of oxidative stress on treatment outcomes. Methods: Biomarkers of oxidative stress (thiobarbituric acid-reactive substances [TBARS]) and antioxidant capacity (glutathione peroxidase [GPx] and glutathione content [thiol]) were prospectively evaluated along with biochemical and clinical data in 100 patients with sepsis on days 1, 4, and 7 after admission. Results: The TBARS level of the non-survivor group was significantly higher than that of the survivor group on day 1 and day 4 and negatively correlated with thiol upon admission. However, thiol was positively correlated with lactate concentration. The TBARS and lactate levels upon admission were independent predictors of fatality. Conclusions: We conclude that a TBARS cut-off value of 18.30 μM can be used to predict fatality, and an increase in the TBARS concentration by 1 μM will increase the fatality rate by 0.94%. In the panel of biomarkers, the TBARS assay can be considered as a prognostic biomarker for the treatment of patients with sepsis.